Pengaruh Konsentrasi Ekstrak dan Maltodekstrin terhadap Antioksidan Enkapsulat Ekstrak Daun Kelor (Moringa Oleifera L.) - Dirgandini, Putu Eka; Wisaniyasa, Ni Wayan; Puspawati, Gusti Ayu Kadek Diah (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 13 No 3 (2024): Jurnal ITEPA, 2024)
Moringa leaf extract can be used as a natural antioxidant to reduce the use of synthetic antioxidants in food. One way to protect the antioxidants of moringa leaf extract is through encapsulation. Encapsulation can extend the shelf life and stabilize moringa leaf extract. The encapsulated product consists of a core material and a channeling material, one of the frequently used channeling materials is maltodextrin. One of the factors affecting encapsulation is the concentration of core material and channeling material. This study aimed to determine the effect of extract and maltodextrin concentration on the antioxidant encapsulated moringa leaf extract produced as well as to know the exact concentration of extract and maltodextrin to produce the best moringa leaf extract encapsulate. This research method uses a Group Random Draft with 2 factors. The first factor is that the concentration of moringa leaf extract consists of 3 levels which are 1%, 1.5%, and 2%. The second factor is the concentration of maltodextrin, which consists of 3 levels: 15%, 20%, and 25%. Interactions between moringa leaf extract concentrations and maltodextrin affect rendering, solubility, antioxidant activity, vitamin C levels, encapsulation efficiency, sensory evaluation (color, aroma, taste, and overall acceptability), and color scoring assays. A concentration of 1% moringa leaf extract and 25% maltodextrin produces the best encapsulation with a rendering characteristic of 86.17%, moisture content of 1.94%, solubility of 94.98%, antioxidant activity of 6.22%, vitamin C content of 7,239.15 mg/100ml, and an encapsulation efficiency of 74.47% as well as having color sensory properties rather like green, aroma rather, regular taste, and the overall reception is rather likable. Keywords: Moringa leaf extract, maltodextrin, and encapsulation